Consumer behavioural intention and consumption towards functional food in Malaysia - Hayatul Safrah, Salleh (2014)
Unhealthy eating behaviour has been linked to the risks of many chronic diseases all around the world including Malaysia. Functional foods and its association with health benefits and reducing the risk of diseases open a promising avenue for consumers to pursue a healthier life as well as extending their life expectancy. This study aims to examine the attitude dimensions, social influence and self-efficacy related factors that may influence consumer-behavioural intention to consume functional foods and to identify the relationship between consumer-behavioural intention and consumer-consumption behaviour as well as to examine the effect of past experience as moderator on the intention-behaviour relationship. By using mall intercept surveys, data were collected from 452 respondents aged 18 and above who shopped at hyperrnarkets in Malaysia. From the analysis undertaken, it was found that the level of consumer-behavioural intention to consume functional food was encouraging and it positively affected the level of functional food consumption behaviour among consumers. The results revealed that perceived reward from using functional food, self-efficacy and necessity for functional food significantly influenced consumer-behavioural intention to consume such food. Findings also showed that feeling of using functional food (dimension of past experience) moderated the relationship between intention and behaviour. Consumer intention towards the consumption of functional food was found to be different across gender, age and marital status. The findings delivered rich insights for the marketers and manufacturers of the functional food industry in formulating effective promotions and marketing strategies that could be aimed at the right consumers. It is hoped that this study will provide beneficial information to the government in enhancing the health promotional campaigns and activities aiming at improving healthy consumption and the health of Malaysians. This study has paved the way for further research that include a study of consumer behaviour towards specific functional food categories with unique components that could cure different health problems or reduce the risk of different disease.